What triggers prosocial effort? A positive feedback loop between positive activities, kindness, and well-being. Issue 4 (4th July 2017) - Layous, Kristin; Nelson, S. Katherine; Kurtz, Jaime L.; Lyubomirsky, Sonja
Abstract: Across two studies, we found evidence supporting a positive feedback loop between positive activities, kindness and well-being. In Study 1, participants were randomly assigned to one of four distinct positive activities (versus a neutral writing activity) before spending three weeks engaging in kind acts. We found that the positive activities served as triggers – that is, they predicted greater prosocial effort, which in turn predicted greater well-being immediately following the intervention and at a two-week follow-up. In Study 2, we explored the specific effects of a gratitude trigger, and extended the intervention period to six weeks. Although, we did not replicate the direct effect of the gratitude trigger on prosocial effort, people who wrote gratitude letters (versus writing about their week) reported relatively greater elevation, which predicted greater prosocial effort during the six weeks. In turn, replicating Study 1, greater effort predicted higher well-being immediately following the study.